Effect of extraction processes on the physicochemical and functional properties of protein-rich extracts from the red seaweed Pyropia Seriata (Nori) - Bohan Zhang; Yaoyao Peng; Pattarasuda Rawiwan; Tom Wheeler; Joshua Fitzgerald; Lee Huffman; Siew Young Quek (Future Foods)
This study examined the physicochemical and techno-functional properties of protein extracts from the red seaweed (Pyropia seriata). The extraction processes involved variations of some of the following steps: alkaline treatment, milling, freeze drying, neutralisation, heating, and concentration. The extracts had total amino acid contents ranging between 40 and 55 % of the powders with essential amino acids comprising 25–30 % of the powders. The extracts were particularly abundant in aspartic acid and limited in the essential sulphur amino acids. The molecular weight (MW) distribution of the proteins within the extracts ranged from <10 to 50 kDa. All the extracts were soluble, with a solubility of 65–100 % depending on the final pH of the solution. The extracts had significant foaming-producing and emulsifying potential. The foaming stability ranged between 75 and 91 % for solutions between pH 7 and 11 and less than 75 % for solutions with pH of 5 or 3. Alkaline treatment significantly improved foaming capacity (120–160 %). A similar effect was also observed for emulsifying activity (0.29–0.51) and emulsifying stability (15–40 %). Milling enhanced the emulsifying potential and decreased the mg of amino acids per g powder. Neutralisation with hydrochloric acid instead of citric acid and subsequent heating and concentration showed minimal effect on the properties of the extracts and decreased the mg amino acids per g powder. This research highlights the potential of Pyropia seriata as a source of soluble alternative protein for food applications.